A Circadian Hygiene Education Initiative Covering the Pre-pandemic and Pandemic Period Resulted in Earlier Get-Up Times in Italian University Students: An Ecological Study - Montagnese, Sara; Zarantonello, Lisa; Formentin, Chiara; Giusti, Gianluca; Mangini, Chiara; Isherwood, Cheryl M.; Ferrari, Paolo; Paoli, Antonio; Mapelli, Daniela; Rizzuto, Rosario; Toppo, Stefano; Skene, Debra J.; et al. (Frontiers in Neuroscience, 2022)
The aims of the present study were to obtain sleep quality and sleep timing information in a group of university students and to evaluate the effects of a circadian hygiene education initiative. All students of the University of Padova (approximately 64,000) were contacted by e-mail (major campaigns in October 2019 and October 2020) and directed to an ad hoc website for collection of demographics and sleep quality/timing information. Participants (n = 5,740) received one of two sets of circadian hygiene advice (“A regular life” or “Bright days and dark nights”). Every month, they were then asked how easy it had been to comply and provided with the advice again. At any even month from joining, they completed the sleep quality/timing questionnaires again. Information on academic performance was obtained post hoc, together with representative samples of lecture (n = 5,972) and examination (n = 1,800) timings, plus lecture attendances (n = 25,302). Fifty-two percent of students had poor sleep quality, and 82% showed signs of social jetlag. Those who joined in October 2020, after several months of lockdown and distance learning, had better sleep quality, less social jetlag, and later sleep habits. Over approximately a year, the “Bright days and dark nights” advice resulted in significantly earlier get-up times compared with the “A regular life” advice. Similarly, it also resulted in a trend toward earlier midsleep (i.e., the midpoint, expressed as clock time, between sleep onset and sleep offset) and toward a decrease in the latency between wake-up and get-up time, with no impact on sleep duration. Significant changes in most sleep quality and sleep timing variables (i.e., fewer night awakenings, less social jetlag, and delayed sleep timing during lock-down) were observed in both advice groups over approximately a year, mostly in association with pandemic-related events characterizing 2020. Early chronotype students had better academic performances compared with their later chronotype counterparts. In a multivariate model, sleep quality, chronotype and study subject (science and technology, health and medical, or social and humanities) were independent predictors of academic performance. Taken together, these results underlie the importance of designing circadian-friendly university timetables.